Nightmare frequency in adults with attention-deficit hyperactivity disorder - Schredl, Michael; Sobanski, Esther (European archives of psychiatry and clinical neuroscience, 2017)
Nightmare frequency in adult ADHD patients has not yet been studied systematically. In a sample of 65 patients, it could be shown that nightmare frequency was elevated in ADHD patients compared to a sample representative for Germany. Frequent nightmares (once a week or more often) were reported by 4.62 % of the patients and 1.77 % of the controls. This increase was neither explained by the increased dream recall in general nor by the presence of a comorbid mental disorder. Questions about nightmares should be included in the diagnostic procedures for ADHD patients, and it should be tested whether well-established nightmare treatment strategies like imagery rehearsal treatment might be beneficial to those patients with nightmares.